Relationship of resistin gene polymorphism (rs7139228) with resistin levels and metabolic syndrome risk in obese subjects - de Luis Román, Daniel; Primo Martín, David; Izaola, Olatz; Aller, Rocío (Nutrición hospitalaria : organo oficial de la Sociedad Española de Nutrición Parenteral y Enteral, 2023)
Background: despite the relationship of resistin with metabolic syndrome (MS), the relationship of the 5'UTR intron C/T variant SNP rs7139228 of the RETN gene with the presence of MS has not been evaluated. Objective: the objective of this study is to evaluate the influence of SNP rs7139228 of the RETN gene on circulating resistin levels, as well as on MS in obese subjects. Material and Methods: a Caucasian population of 1003 obese subjects was enrolled. An anthropometric evaluation (weight, waist circumference, fat mass), evaluation of nutritional intake, biochemical study (glucose, insulin, C-reactive protein, lipid profile, insulin, HOMA-IR, resistin) and rs7139228 genotype was carried out. Results: genotype distribution was: 852 subjects with GG (84.9 %), 147 subjects with GA (14.7 %) and 4 subjects with AA (0.4 %). The allelic frequency was G (0.92) and A (0.08). Serum levels of resistin (delta: 1.7 ± 0.2 ng/ml; p = 0.01), insulin (delta: 4.2 ± 0.4 IU/L; p = 0.01) and HOMA-IR (delta: 1.9 ± 0.2 units; p = 0.03) were higher in patients carrying the A allele than in non-carriers. The overall prevalence of MS was 48.1 %. A logistic regression analysis showed a high percentage of hyperglycemia (OR = 1.60, 95 % CI = 1.08-2.96; p = 0.02) and metabolic syndrome (OR = 1.33, 95 % CI = 1.07-3.39, p = 0.02) in carriers of the A allele after adjusting for resistin levels, sex, BMI and age. Conclusions: the A allele of the genetic variant rs7139228 is associated with higher levels of resistin, basal insulin, insulin resistance, and prevalence of metabolic syndrome in obese subjects.